1982
DOI: 10.1111/j.1151-2916.1982.tb10485.x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Conductivity, Seebeck Coefficient, and Defect Structure of LaFeO3

Abstract: Electronic conductivity and Seebeck coefficients of LaFeOJ were measured as a function of temperature (1000" to 1400°C) and P ( 0 2 ) (10' to Pa). Electronic conduction was found to be n-type in the lower P(Oz) range, and p-type in a higher P ( 0 2 ) range. The calculated carrier mobilities suggest a hopping-type conduction mechanism. The carrier concentrations were calculated as a function of P(Oz) and the defect structure was described. It was found that the electrical properties of LaFeOJ are determined not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(88 citation statements)
references
References 9 publications
7
80
1
Order By: Relevance
“…27,28,32 P-type (in air) and n-type (reducing conditions) semiconductor behaviour has previously been reported for several related Fe-containing perovskites, including La 1Àx Sr x FeO 3Àd [33][34][35] and LnFeO 3 (Ln = Pr, Nd, Sm, Eu and Gd). 36,37 In these materials the electronic conductivity is strongly linked to polaron hopping and the oxidation state of Fe, which is strongly dependent on the partial pressure of oxygen ( p(O 2 )).…”
Section: +mentioning
confidence: 85%
“…27,28,32 P-type (in air) and n-type (reducing conditions) semiconductor behaviour has previously been reported for several related Fe-containing perovskites, including La 1Àx Sr x FeO 3Àd [33][34][35] and LnFeO 3 (Ln = Pr, Nd, Sm, Eu and Gd). 36,37 In these materials the electronic conductivity is strongly linked to polaron hopping and the oxidation state of Fe, which is strongly dependent on the partial pressure of oxygen ( p(O 2 )).…”
Section: +mentioning
confidence: 85%
“…11-14 Perovskite oxides of the type ABO 3 with high electrical conductivity have been studied for use as electrode materials for several electrochemical and thermal processing applications. 15 MIZUSAKI et al 16 reported the relation between the conductivity of LaFeO 3, oxygen partial pressure (Po2), and temperature T. It was shown that the mechanism of electrical conduction in the lower PO2 range can be attributed to the hopping of electrons between FeFe' and FeFex and in the higher PO2 range to the hopping of electrons between FeFe x and FeFe'. Also, it was shown that the concentration of p-type carrier, FeFe' , in the higher P02 range can be related to [VLa'"] and so a slight deviation from unity in the La/Fe ratio greatly affects the conductivity.…”
Section: -5731/99/usd 17 O0 9 1999 Akadomiai Kiad6 Budapestmentioning
confidence: 97%
“…where [26][27][28] Thus, in the case of localized charge carriers, the electrical conduction can be realized through the polaron hopping mechanism. 16,17,27,28 Alternatively, in recent DFT studies 14,15,29 the possibility of band-like semiconductor behavior has been suggested for the same class of materials in which the case of delocalized charge carriers can also be feasible.…”
mentioning
confidence: 99%
“…16,17,27,28 Alternatively, in recent DFT studies 14,15,29 the possibility of band-like semiconductor behavior has been suggested for the same class of materials in which the case of delocalized charge carriers can also be feasible. 29 In our experiments, the strong dependence of the conductivity with respect to partial pressure of oxygen was observed for x > 10% BFO, see Figs.…”
mentioning
confidence: 99%